Die Rolle der Schöffen bei Absprachen im Strafprozess Ergebnisse einer Befragung von knapp 9.000 Laienrichtern - Iberl, Benedikt (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The study examines how lay judges experience the still controversial plea bargains in criminal proceedings. For the purpose, almost 9000 lay judges from all German states were surveyed. The study confirms previously existing findings according to which illegal plea bargaining continues to be a widespread issue. Additionally, it is precarious that lay judges rarely have the influence on the outcome of criminal proceedings that they should have. Instead, they are often reduced to the status of mere extras. Another result of the survey, however, was more encouraging: A clear majority of lay judges consider their office to be important. That said, even though most lay judges are satisfied with their work, they still propose numerous avenues to improve the status quo.